GIS-based Studies in the Humanities and Social Sciences - Okabe, Atsuyuki (CRC Press, 2009)
Studies in the humanities and the social sciences can be enhanced through the use of geographic information systems (GIS). However, this computer-aided method of analysis is worthless unless researchers can devote the time necessary to learn what it is, what it can do, and how to use it.